RELATIONSHIP OF ENVIRONMENTAL PHYSICAL FACTORS AND LIQUID INTAKE WITH HYDRATION STATUS OF LONTONG HOME INDUSTRY SURABAYA - Ahmad Luqmanul Hakim; Lilis Sulistyorini (The Indonesian Journal of Public Health, 2021)
A hot working environment can cause health problems for workers, one of them being dehydration. The hydration status of a worker can be influenced by the characteristic of the worker, physical environmental factors, and fluid intake. The objective of this study is to determine the relationship between workers’ characteristics, physical environmental factors, and fluid intake with the hydration status of workers. This study was conducted using the cross-sectional design method and used a simple random sampling technique to select  17 respondents and 17 home industries originally derived from 20 respondents and 20 home industries. The research location was on Jalan Banyu Urip Lor X Surabaya. Data were analyzed using cross-tabulation and fisher’s exact test with a confidence level of 95%. The data were collected through interviews, measurements, questionnaires, and verification. The results showed that there was a significant relationship between physical environmental factors, which included temperature (p = 0.002), humidity (p = 0.029), and fluid intake (p = 0.029), with the hydration status of workers. In general, it can be concluded that physical environmental factors and fluid intake are relevant towards the hydration status of workers. Therefore, it is recommended that the workers improve air circulation in the room by adding natural ventilation, an exhaust fan in the kitchen, and are advised to consume enough mineral water while working.Keywords: temperature, humidity, fluid intake, hydration status